What do we know about the sleep effects of caffeine used to treat apnoea of prematurity? A systematic review of the literature - Ana Renata Pinto de Toledo; Higor Arruda Caetano; Jovito Adiel Skupien; Carina Rodrigues Boeck; Humberto Fiori; Rosane Souza da Silva (SpringerOpen, 2023)
Abstract Objective Scientific scrutiny has proved the safety and benefits of caffeine to treat apnoea of prematurity (AOP). However, there is no consensus on the effects of this treatment on sleep, especially considering the key role of adenosine and early brain development for sleep maturation. We systematically reviewed studies with sleep as a primary and/or secondary outcome or any mention of sleep parameters in the context of caffeine treatment for AOP. Methods We performed a systematic search of PubMed, Web of Science and the Virtual Health Library from inception to 7 September 2022 to identify studies investigating the short- and long-term effects of caffeine to treat AOP on sleep parameters. We used the PIC strategy considering preterm infants as the Population, caffeine for apnoea as the Intervention and no or other intervention other than caffeine as the Comparison. We registered the protocol on PROSPERO (CRD42021282536). Results Of 4019 studies, we deemed 20, including randomised controlled trials and follow-up and observational studies, to be eligible for our systematic review. The analysed sleep parameters, the evaluation phase and the instruments for sleep assessment varied considerably among the studies. The main findings can be summarised as follows: (i) most of the eligible studies in this systematic review indicate that caffeine used to treat AOP seems to have no effect on key sleep parameters and (ii) the effects on sleep when caffeine is administered earlier, at higher doses or for longer periods than the most common protocol have not been investigated. There is a possible correlation between the caffeine concentration and period of exposure and negative sleep quality, but the sleep assessment protocols used in the included studies did not have high-quality standards and could not provide good evidence. Conclusions and implications Sleep quality is an important determinant of health, and better investments in research with adequate sleep assessment tools are necessary to guarantee the ideal management of children who were born preterm.